The effect of silane as coupling agent on the polyurethanes filled silica / Noor Khairin Mohd ... [et al.] - Mohd, Noor Khairin; Ahmad, Sahrim; Zakaria, Sarani; Ali, Ernie Suzana (2002)
Palm kernel oil -based polyol with the hydroxyl number 350-370 mg/KOH and functionality of 2.5-3.0 was used to produce rigid polyurethane foam after added with diisocyanate, surfactant and catalyst. Silica filler was mixed into the formulation of polyurethane and varied from 0, 2, 4, 6 and 8 wt.%. The concentration of silane as coupling agent were varied from 2, 2.5 and 3%. The bonding between resin and filler was investigated at various percentage of filler content. The result has shown that the compressive strength increased with the addition of silane concentration.